2017
DOI: 10.1017/s1041610217001132
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ attitude toward disclosure of Alzheimer's disease diagnosis in Urban China

Abstract: This study suggests most of the well-educated individuals in a Chinese urban area favored disclosing the diagnosis when they or their family members were diagnosed with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…The relationship between education level and dementia knowledge level found in this study is consistent with that reported in previous studies [18,19,24,62]. People living in urban areas had a higher knowledge level of dementia than those living in rural areas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The relationship between education level and dementia knowledge level found in this study is consistent with that reported in previous studies [18,19,24,62]. People living in urban areas had a higher knowledge level of dementia than those living in rural areas.…”
Section: Discussionsupporting
confidence: 92%
“…In China, several studies exploring the dementia-related knowledge of different groups, such as community residents [22,23], family and hospital caregivers [12,24], and nursing assistants [25] have been conducted. Different groups of people have different levels of dementia knowledge, which are associated with region, education, experience of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of genotype testing, coupled the increasing prevalence of AD, present a likely scenario that APOE disclosure will become increasingly sought after by healthy individuals. Indeed, results from recent studies in both Western and Asian populations indicated that a majority of older adults preferred to be informed about a diagnosis of AD or dementia (van den Dungen et al, 2014;Zou et al, 2017). There is thus a pressing need for a better understanding of how APOE disclosure affects healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that there are significant differences between the end-of-life practices in China and some Western countries, especially regarding illness disclosure. 11,12 Cultural and national differences in informing patients regarding the nature and severity of their illness have been widely reported. Family pressures and concerns about discouraging the patient were cited as the reasons for nondisclosure.…”
Section: Discussionmentioning
confidence: 99%
“…In China, individuals make important personal decisions, such as regarding, for example, marriage or careers, in consultation with family members. 10,11…”
Section: Introductionmentioning
confidence: 99%